Bridging Local Innovations and Global Challenges in STEM Education - Kusmawan, Udan (Universitas Terbuka, 2024)
The November 2024 edition of the International Journal of Research in STEM Education (IJRSE) presents a curated collection of eight articles that explore the dynamic intersection of local innovations and global challenges within STEM education. This issue features contributions from 12 universities located across five countries and spanning three continents, illustrating the global scope and diverse perspectives that inform current STEM educational practices. The articles delve into various themes, including the effective integration of indigenous knowledge systems alongside modern educational techniques, the implementation of cutting-edge pedagogical strategies, and the crucial importance of fostering inclusivity and accessibility within STEM fields. Through a detailed examination of these topics, this issue not only highlights the unique contributions of different educational contexts but also underscores the universal challenges and opportunities that shape STEM education in today's interconnected world.